Evaluation Virtual Assistant Chatbot Acceptance with an Unified Technology Acceptance and Use of Technology-Based Model - Sabila, Radhiya; Pratama, Arista; Safitri, Eristya Maya (Journal of Information System and Informatics, 2024)
The virtual assistant chatbot in the MyTelkomsel application is a company's effort to achieve goals and improve business performance. Chatbot as a virtual assistant has advantages and disadvantages. Evaluating user acceptance of the Virtual Assistant Chatbot in the MyTelkomsel application is important to overcome so that users do not switch to using other products. One of the models used to evaluate user acceptance of information systems is the Unified Theory of Acceptance and Use of Technology (UTAUT). UTAUT is able to explain how the use of technology can be influenced by individual differences in use. The conclusion of this study is that the variables that influence the acceptance of the use of virtual assistant chatbots in the MyTelkomsel application consist of the greatest influence is shown in the effect of social influence on Behavioural intention with a value of 5,768. Then the second largest influence is the trust variable on behavioural intention with a value of 5,220. Meanwhile, the variable that has the smallest influence on behavioural intention is effort expectancy with a value of 5,134.